SLC4A2 Deficiency Causes a New Type of Osteopetrosis. (11th November 2021) - Xue, Jing‐Yi; Grigelioniene, Giedre; Wang, Zheng; Nishimura, Gen; Iida, Aritoshi; Matsumoto, Naomichi; Tham, Emma; Miyake, Noriko; Ikegawa, Shiro; Guo, Long
ABSTRACT: Osteopetrosis is a group of rare inherited skeletal disorders characterized by a marked increase in bone density due to deficient bone resorption. Pathogenic variants in several genes involved in osteoclast differentiation and/or function have been reported to cause osteopetrosis. Solute carrier family 4 member 2 ( SLC4A2, encoding anion exchanger 2) plays an important role in osteoclast differentiation and function by exchange of Cl − with HCO3 − . Biallelic Slc4a2 loss‐of‐function mutations in mice and cattle lead to osteopetrosis with osteoclast deficiency; however, pathogenic SLC4A2 variants in humans have not been reported. In this study, we describe a patient with autosomal recessive osteopetrosis due to biallelic pathogenic variants in SLC4A2 . We identified novel compound heterozygous variants in SLC4A2 (NM_003040.4: c.556G>A [p.A186T] and c.1658T>C [p.V553A]) by exome sequencing. The measurement of intracellular Cl − showed that the variants decrease the anion exchange activity of SLC4A2. The impact of the variants on osteoclast differentiation was assessed by a gene knockout‐rescue system using a mouse macrophage cell line, RAW 264.7. The Slc4a2 ‐knockout cells show impaired osteoclastogenesis, which was rescued by the wild‐type SLC4A2, but not by the mutant SLC4A2s. Immunofluorescence and pit assay revealed that the mutant SLC4A2s leads to abnormal podosome belt formation with impaired bone absorption. This is the first report on an individual affected by SLC4A2 ‐associated osteopetrosis (osteopetrosis, Ikegawa type). With functional studies, we prove that the variants lead to SLC4A2 dysfunction, which altogether supports the importance of SLC4A2 in human osteoclast differentiation. © 2021 American Society for Bone and Mineral Research (ASBMR).